Formulasi Tepung Mocaf dan Tepung Ikan Patin Terhadap Kualitas dan Nilai Gizi Cookies Mocaf Patin - Afina Amalia Nurfajrina; Widi Hastuti (JGK:Jurnal Gizi dan Kesehatan, 2021)
Background : The problem of nutrition for pregnant women KEK is the focus of attention in Indonesia. Based on the results of Riskesdas 2018, the prevalence of KEK risk in pregnant women in West Java was 14.1%, the highest prevalence of KEK was at the age of pregnant women (15-19 years) with a prevalence of 33.5%. KEK pregnant women are required to consume additional food to overcome malnutrition. The use of catfish meal in the manufacture of cookies products will increase the protein content and increase the nutritional content of a product. The Purpose : The purpose of this study was to determine the effect of mocaf flour and catfish meal formulations on the quality and nutritional value of mocaf patin cookies as additional food for pregnant women in KEK. This research was conducted in 2020 at the Health Ministry of Health Bandung, Department of Nutrition. Methods : This research is experimental with three treatments between mocaf flour and catfish meal 80%: 20%, 70%: 30% and 55%: 45% and organoleptic testing was carried out on 30 panelists. Conclusion : Cookies with 80% formula: 20% have better acceptance compared to other formulas. Based on the calculation of the nutritional value per serving (100 gr), the 80%: 20% formula cookies contain 612.40 kcal of energy, 9.39 grams of protein, 33.30 grams of fat, and 69.79 grams of carbohydrates. For the development of this cookie product, it is necessary to test Fe in laboratory tests so that the calculation of nutritional value is more accurate.